Formulasi sabun karika (Carica pubescens) sebagai sabun kecantikan dan kesehatan - Roisatul Ainiyah; Cahyaning Rini Utami (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
Soap is a mixture of sodium compounds with fatty acids that are used as a body cleansing agent, in the form of solid, foam, with or without other additives and does not cause irritation to the skin. To improve quality, bath soap can be given additional ingredients that contain vitamins and various nutrients needed by the skin such as the addition of extracts of karika fruit (Carica pubescens). The purpose of this research is to find out the right formulation in making karika soap. This research used an experimental method with randomized block design (RCBD), consisting of two factorial variations in the concentration of karika juice (0%, 100%, 80%, 60%) and variations in the concentration of NaOH (30%, 35%, and 40% ) so that 12 treatments were obtained each with 3 replications. The process of making soap uses the hot process method. Soap quality analysis is carried out by comparing the results of chemical tests for karika soap with SNI 06-3532-1994 (SNI for solid bath soap), foam stability test, soap hardness, and organoleptic test. The data obtained were analyzed using ANOVA with a confidence interval of 5%. If an effect is found on one of the variebel, a further Tukey test is performed. The results showed that the water content, pH, and free alkali did not meet SNI, while the amount of fatty acids and mineral oil was in accordance with SNI, the significant difference between treatments was only in the water content. Karika soap has abundant and stable foam. The higher concentration of karika juice make the lower hardness of the soap. Organoleptic test results showed a low level of preference for panelists on karika soap products. The suggestion from this research is that karika juice can be tried to applied it in the liquid bath.